Synthesis and biological evaluation of pyranocarbazole derivatives as Anti-tumor agents. (1st February 2021) - Liu, Ke; Zang, Yingda; Shen, Cangjie; Li, Chuangjun; Ma, Jie; Yang, Jingzhi; Sun, Xingyan; Chen, Xinyi; Wang, Nan; Zhang, Dongming
Graphical abstract: Abstract: A series of pyrano[3, 2- a ]carbazole alkaloids were designed and synthesized as derivatives of Girinimbine. The anticancer activities of these derivatives (3, 4a-j, 5a, 5c, 5f, 5i, 6c, 7a, 7c, 7f, 7i) against 10 cancer cell lines were studied. Among them, compounds 3 and 7i with N-methyl piperazine showed significant anticancer activity against MCF-7 cell lines with the IC50 values of 1.77 and 4.32 μM, respectively. Furthermore, their effects on altering cell morphology, inducing cell cycle arrest and apoptosis in MCF-7 cells were studied in vitro . In addition, the molecular docking study was carried out by using Discovery Studio software to predict the interactions between these derivatives and tubulin. All in all, these consequences reveal that pyranocarbazole derivatives with N-methyl piperazine can be used as potential anticancer lead compounds and provide useful points for the further optimization of pyranocarbazole alkaloids.